Vojni spopadi po televiziji - Jakopič, Kaja (Monitor ISH, 2004)
War conflicts on television. The reality of war conflicts is presented to TV viewers in a highly segmented and concentrated manner. The choice of conflicts to be shown often rests with governments, international corporations, and ideology. The portrayal of televised wars is based on simplification, stereotypes, replaying, and visual manipulation.
Keywords: mass media; množični mediji; informiranje; television; televizija; vojna; war; vizualizacija vojne; zalivska vojna; cenzura; propaganda